PENCIPTAAN BUSANA PESTA MUSLIM DENGAN INSPIRASI TARI JARANAN TURONGGO YAKSO DI TRENGGALEK - Risma Juliarus Vidia Sari; Deny Arifiana (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The development of modest wear trends in Indonesia is currently still dominated by modern global motifs that tend to be uniform, necessitating design innovations capable of exclusively representing the values of local cultural arts. This creative research aims to describe the design process, product realization, and presentation techniques of a Muslim family festive wear collection inspired by the visual assertiveness characteristics of the Jaranan Turonggo Yakso Dance from Trenggalek Regency. The method employed in this artistic creation is the Practice-Led Research approach, which encompasses four operational stages, namely: (1) exploration or pre-design of the idea concept, (2) visual draft design of the collection, (3) sewing product realization, and (4) presentation or dissemination of the works. The results of this creative research are a three-piece premium collection intended for a family target market (adult male, adult female, and young boy), utilizing a harmonious palette of emerald green, ivory, and black. The expressive character of the dance's whip strokes is transformed into decorative details using structural cording textile manipulation techniques, combined with asymmetrical hanging overskirt panels and rhythmic teardrop sequin accents. The final stage of work presentation was conducted through product dissemination at the Grand Jury Event and the Annual Fashion Show "MADJADHIKARA" 2025 as a means of commercialization and preservation of traditional culture through modern fashion products.